Long-term multidecadal data from a prairie-pothole wetland complex reveal controls on aquatic-macroinvertebrate communities - Kyle I. McLean (Elsevier, 2021)
Interactions between climate and hydrogeologic settings contribute to the hydrologic and chemical variability among depressional wetlands, which influences their aquatic communities. These interactions and resulting variability have led to inconsistent results in terms of identifying reliable predictors of aquatic-macroinvertebrate community composition for depressional wetlands. This is especially true in the Prairie Pothole Region of North America where, in addition to pronounced climate variability, studies are often confounded by fish introductions. We used environmental monitoring data collected over a 24-year period from a complex of sixteen depressional wetlands and structural equation modeling techniques that incorporated theoretical and empirical relationships outlined in the Wetland Continuum to identify key environmental (climate and hydrogeologic setting) and biotic (competition and predation) drivers of aquatic-macroinvertebrate community composition for prairie-pothole wetlands. Uplands in the study area were primarily native prairie, thus, embedded wetlands were impacted minimally by agricultural influences. Additionally, study wetlands were predominately fishless. In the absence of the overwhelming influence of fishes, major drivers influencing aquatic-macroinvertebrate communities were revealed through the use of data spanning multidecadal-long climate cycles. We found variables related to the placement of wetlands along axes of the Wetland Continuum, e.g., hydrogeologic setting (relative wetland elevation) and hydroclimatic setting (proportion of wetland ponded), to be influential drivers of within-wetland habitat characteristics, such as the proportion of open-water area, which in turn was the strongest predictor of macroinvertebrate community composition. In contrast, predatory invertebrate and salamander abundance and non-predatory invertebrate biomass (i.e., predation and competition) were found to have minimal influence on community composition.